Aerobic economy and competitive performance of U.S. elite swimmer - van Handel, P. J.; Katz, A.; Morrow, J. R.; Troup, J. P.; Daniels, J. T.; Bradleym P. W. (Swimming Science V, 1988)
The sport of swimming presents a unique challange to the measurement of energy cost. Although tethered swimming has provided information on the maximal physiological status of athletes (Bonen, Wilson, Yarkony, & Belcastro 1980; Costill, 1966; Costill et al., 1985), Magel and Faulkner (1%7) found that in trained swimmers tethered values were significantly less than those obtained in free swimming. There is also some question as to the reliability and validity of extrapolation techniques (Costill et al., 1985;. Leger, Seliger, & Brassud, 1980). In a homogenous group of runners, V02max was also a poor discriminator of competitive success (Conley & Krackenbull, 1980; Costill, Branam, Eddy, & Sparks, 1971; Foster, Costill, Daniels, & Fink, 1978; Pollock, Jackson, & Pate, 1980; Sjodin, & Svedenhag, 1985). Other variables such as the fractional utilization of maximal aerobic capacity (Costill, Thomason, & Roberts, 1973; Sjodin & Svedenhag, 1985) or the economy of effort (Daniels, 1974; Daniels, Krahenbuhl, Foster, Gilbert, & Daniels, 1977; McMiken & Daniels, 1976; Pollock et al., 1980; Powers, Dodd, Deason, Byrd, & McKnight, 1983) may be at least as important for competitive success. This chapter describes a method for determining oxygen cost in free swimming and quantifies aerobic economy of submaximal swimming and its relationship to competitive efforts of world-class swimmers.